Pengaruh Perceived Organizational Support Terhadap Kinerja Karyawan Melalui Employee Engagement: Sebuah Studi Literatur - Budi Prastyo (Prodi Manajemen Fakultas Ekonomi Universitas Hasyim Asy'ari Tebuireng Jombang, 2020)
This study aims to determine the influence of perceived organizational support on employee performance through employee engagement. Literature studies are based on 15 national and international journal and data are collected using search engine methods. The results showed that perceived organizational support have a positive effect on employee performance and employee engagement plays an important role in supporting this influence. If the perceived organizational support is high it will add to the employee’s engagement and will had a positive on employee performance.